Hubungan Pengetahuan Dan Kunjungan Ibu Dengan Konsumsi Vitamin A Pada Ibu Nifas di Wilayah Kerja Puskesmas Aek Parombunan Kota Sibolga Tahun 2023 - Betty Novalina Simanjuntak; Magdalena Br Barus (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
One of the postpartum services provided to postpartum mothers includes the provision of Vitamin A 200,000 SI capsules twice. This research aims to determine the relationship between maternal knowledge and visits and vitamin A consumption among postpartum mothers in the working area of ​​the Aek Parombunan Health Center, Sibolga City in 2023. This type of research a cross sectional design. Population are postpartum mothers who visited the Aek Parombunan Health Center, Sibolga City, are 100 people. The results of this research are that there is a relationship between knowledge and vitamin A consumption among postpartum mothers in the working area of ​​Aek Parombunan Health Center, Sibolga City in 2023 with a p-value of 0.03 and there are maternal visits with vitamin A consumption among postpartum mothers in the working area of ​​Aek Parombunan City Health Center. Sibolga in 2023 with a p-value of 0.003. It is recommended for health workers, especially midwives, to further improve counseling at every postpartum mother's examination, especially regarding vitamin A so that coverage of vitamin A administration can reach the target of 100%